Low‐loss and broadband InP mirror‐based out‐of‐plane optical coupler. Issue 5 (5th March 2023) - Saito, Yusuke; Ueda, Yuta; Shindo, Takahiko; Kurata, Yu; Kanazawa, Shigeru; Kobayashi, Wataru; Ishikawa, Mitsuteru
Abstract: The authors developed a mirror‐based out‐of‐plane optical coupler (MOOC) for InP photonic integrated circuits (PICs). The coupler has the coupling loss and alignment tolerance comparable to those of a conventional edge coupler. An asymmetric Mach–Zehnder interferometer (a‐MZI) with the MOOC exhibits little wavelength‐dependent loss (WDL) and a high extinction ratio (ER) of >20 dB over 100‐nm wavelength bandwidth. In addition, the temperature‐independent transmittance spectra were obtained. Finally, the authors fabricated a 4‐ch MOOC array with the pitch of 40 μm, which corresponds to the core pitch of practical multi‐core fibre (MCF). Abstract : We developed a mirror‐based out‐of‐plane optical coupler (MOOC) for InP photonic integrated circuits. The coupler has the coupling loss and alignment tolerance comparable to those of a conventional edge coupler. A small wavelength‐dependent loss was observed over the 100‐nm wavelength bandwidth at chip temperatures of 25, 45, and 65°C.